Intra-Industry Effects of the Accident at Three Mile Island - Bowen, Robert M.; Castanias, Richard P.; Daley, Lane A. (Journal of Financial and Quantitative Analysis, 1983)
Robert M. Bowen, Richard P. Castanias, Lane A. Daley, Intra-Industry Effects of the Accident at Three Mile Island, The Journal of Financial and Quantitative Analysis, Vol. 18, No. 1 (Mar., 1983), pp. 87-111